Activating aspirations: Fostering creative and soft skills for rural NEETS in central Portugal - Ribeiro, A. S.; Roque, I.; Sousa, J. C. (Journal of Human Development and Capabilities, 2025)
This article focuses on young people not in employment or education in rural areas of Portugal. It highlights the specific vulnerability of this group, and its conceptual focus is underpinned by the debate between the capabilities approach and structural ramifications in the labour market. It presents a case study analysis based on an employability and social inclusion programme for young people in Central Portugal. The data analysis comprises documentary analysis, interviews with PES services and case workers, and 13 semi-structured interviews with young people. The discussion, which covers the views of programme participants’ and stakeholders, deconstructs generalisations about the labour market and employment prospects for higher education graduates, taking the capabilities for education, work, voice and aspirations as analytical points. We argue that rural young people’s employability may be enhanced by non-formal training that stimulates entrepreneurial and soft skills, and that service delivery should take mobility into account when planning interventions in rural areas.